The therapeutic approaches in children and adolescent with Tourette’s disorder - Yoo-Sook Joung; Moon-Soo Lee (Precision and Future Medicine, 2021)
A tic is a sudden, rapid, recurrent, and nonrhythmic motor movement and vocalization. In Tourette’s disorder (TD), the tics may wax and wane in frequency and severity but persist for more than one year since the first tic onset. TD may have a high spontaneous remission rate. However, in some patients, tic symptoms persist even after adulthood. Since tic symptoms develop from a very young age and have wax and wane patterns during the development period, uncontrolled symptoms can cause both subjective distress and functional disability in activities of daily living. Even if psychoeducation and behavioral therapy are considered first, the treatment is determined by considering various factors such as severity of symptoms, subjective distress, physical pain, and functional impairment caused by symptoms. In addition to the antipsychotics that have been used so far, several drugs have recently been tried based on the pathogenesis hypothesis, and the evidence for treatment effects is increasing. This article reviewed possible interventions with proven evidence of TD, including psychopharmacologic treatment.